High-selectivity palladium catalysts for the partial hydrogenation of alkynes by gas-phase cluster deposition onto oxide powders. (3rd April 2018) - Ellis, Peter R.; Brown, Christopher M.; Bishop, Peter T.; Ievlev, Dmitrij; Yin, Jinlong; Cooke, Kevin; Palmer, Richard E.
ABSTRACT: The selective hydrogenation of alkynes is an important reaction in the synthesis of fine and bulk chemicals. We show that the synthesis of metal nanoparticles in the gas phase, followed by deposition onto conventional support powders results in materials that perform as well as those made by typical methods for making catalysts (impregnation, deposition). The nature of the active sites in these catalysts is explored. Graphical Abstract: